Development of black cumin seed oil (Nigella sativa L.) SNEDDS into solid-SNEDDS and its characterization - Rodhia Ulfa; Dwi Utami; Iis Wahyuningsih (Pharmaciana, 2021)
Black cumin seed oil (MBJH) (Nigella sativa L.) is a well-known herb with pharmacology activities such as anticancer and anti-thrombocytopenia. The limitation of MBJH has poor absorption when using oral dosage form. The liquid SNEDDS (Self-nanoemulsifying drug delivery system) of MBJH as an alternative formulation. However, the disadvantage of liquid-SNEDDS of MJBH was the interaction between the active ingredients with soft gelatin capsules. Hence, this study proposed to develop solid-SNEDDS as a new formulation of MBJH. Solid-SNEDDS of MBJH was prepared from liquid-SEDDS of MBJH by adsorption to solid carrier method, consisting of aerosil and crospovidone as the adsorbent. The characterization of S-SNEDDS was determined by emulsification time and percent transmittance. Micromeritics properties of S-SNEDDS such as the angle of repose, bulk and tap density parameter, compressibility index, and Hausner ratio were measured  before and after stored in stress condition (40 ̊ C ± 2 ̊ C and relative humidity of 75% ± 5% for 14 days). The result showed S-SNEDDS of MBJH with aerosil absorbent had better S-SNEDDS performance in both characteristics and micromeritics properties under stress conditions than crospovidone absorbent. In conclusion, the s-SNEDDS of black cumin oil by solid aerosil carrier method is promising for future research development of S-SNEDDS dosage form.